GEOTHERMAL TECHNOLOGIES AS THE BASIS OF SUSTAINABLE AGRIBUSINESS: AN INNOVATIVE APPROACH TO ORGANIC PRODUCTION - YURKO, Ihor; TKACHENKO, Alina; USTIAN, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates the role of geothermal technologies as a strategic foundation for the development of sustainable agribusiness and organic agricultural production in the context of global climate change, energy insecurity, and the implementation of the United Nations Sustainable Development Goals, particularly SDG 2 (Zero Hunger) and SDG 13 (Climate Action). The study focuses on the application of geothermal energy for greenhouse-based organic farming as an environmentally safe and economically viable alternative to conventional heat sources such as natural gas and electricity. The research provides a comparative analysis of energy consumption and operating costs associated with different heating systems used in greenhouse production. The results demonstrate that geothermal heat supply ensures significant cost savings, reduces greenhouse gas emissions, and contributes to long-term energy autonomy of agricultural enterprises. In addition to economic efficiency, geothermal energy enables the maintenance of a stable microclimate in greenhouses, which is critical for meeting organic production standards and improving crop yields throughout the year. Special attention is paid to international experience in the agricultural use of geothermal resources, with examples from Turkey, Iceland, Hungary, China, and other countries where geothermal technologies have been successfully integrated into greenhouse vegetable production, food processing, and agricultural drying systems. The article also analyzes the current state and prospects of geothermal energy development in Ukraine, emphasizing the potential use of depleted oil and gas wells as cost-effective sources of geothermal heat. The findings highlight that the integration of geothermal technologies into organic agriculture not only enhances environmental sustainability but also increases the competitiveness of agricultural producers by reducing dependence on fossil fuels and volatile energy markets. The study concludes that geothermal energy represents a promising innovation-driven pathway for the sustainable transformation of agribusiness in Ukraine and supports further research into regional geothermal potential, investment mechanisms, and technological modernization of greenhouse infrastructure.